Intensification of leaching of uranium concentrates - Mukhachov, A.P.; Kharytonova, Е.А. (Вопросы атомной науки и техники, 2018)
In work results of experiments on a lixiviation of a concentrate of uranium are explained. It is shown that transfer of process of a lixiviation to the pulsation device allows to intensify it, to reduce losses of uranium and hydrogen nitrate and to reduce process temperature. The pulsation device allows to automate process and to provide positive control to them. Викладені результати експериментів з вилуговування концентрату урану в азотній кислоті. Показано, що пульсуюча колона дозволяє інтенсифікувати процес вилуговування урану, скоротити його втрати, витрати азотної кислоти і знизити температуру процесу. Пульсаційні колони дозволяють автоматизувати процес. Изложены результаты экспериментов по выщелачиванию концентрата урана в азотной кислоте. Показано, что пульсирующая колонна позволяет интенсифицировать процесс выщелачивания урана, сократить его потери, расход азотной кислоты и снизить температуру процесса. Пульсационные колонны позволяют автоматизировать процесс.